2006
DOI: 10.1093/europace/eul100
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a high output/short duration radiofrequency current application technique in segmental pulmonary vein isolation for atrial fibrillation

Abstract: Segmental PV isolation using a high power output and short application time is safe and effective in PV isolation in patients with AF. This technique can significantly reduce the procedure and fluoroscopy time compared with a low-power output technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 13 publications
1
87
0
1
Order By: Relevance
“…However, none of these studies were large enough to examine the occurrence of rare complications, such as atrioesophageal fistulas or PV stenosis. Nilsson et al compared ablations using 30 W for 120 seconds to 45 W for 20 seconds . Long‐term outcome and complications were identical in these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies were large enough to examine the occurrence of rare complications, such as atrioesophageal fistulas or PV stenosis. Nilsson et al compared ablations using 30 W for 120 seconds to 45 W for 20 seconds . Long‐term outcome and complications were identical in these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, RF applications of lower power and longer duration result in larger dissipation of RF energies deep into the tissues due to conductive heating and exponential decay of RF energy causing tissue destruction at greater depths. (Figure ) Hence, there is a risk of collateral tissue damage. This has been validated in in‐vivo animal studies where the longer duration ablations had resulted in more steam‐pops and adjacent lung injury during PVI .…”
Section: An Appraisal Of the High‐power Short Duration Strategymentioning
confidence: 99%
“…The first‐in‐human comparison of high‐power with a low‐power ablation strategy was in 2006, when it was studied for segmental PVI . The study employed powers of 45 W/55°C/20 seconds and reported comparable safety and efficacy with standard RF settings (30 W/50°C/120 seconds) with no major complications in either arm.…”
Section: Validation Of Hpsd Rfa In Humansmentioning
confidence: 99%
“…Clinical studies using HPSD ablation are limited. In the earlier days of AF ablation, one group reported that a high‐output (45 W) and shorter‐duration (20 seconds) ablation was equivalent to standard ablation (30 W, 120 seconds) for long‐term AF control (after median 15 months, 74% vs 76% AF‐free). They showed a 25% reduction in the procedure time and radiation dose simply by changing ablation parameters.…”
mentioning
confidence: 98%